Execution efficiency research of different ways of serves in the beach volleyball men's teams competitive activity - A.Y. Melnyk; Y.Y. Strelnykova (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
Purpose: to develop the technique for assessment of quantitative indicators of execution efficiency of serves in competitions of beach volleyball league in Kharkiv among men's amateur teams. Material and methods: the analysis of statistical data, which are obtained as a result the pedagogical observations of power jump serves and aimed serves in 25 games of these competitions, is carried out (with total number of serves 2055). The following methods were used: analysis of scientific-methodical literature; pedagogical observation, methods of mathematical statistics. Results: calculated: distributions of power jump serves and aimed serves according to a certain four-point rating scale; quantitative indicators of execution efficiency of serves which are generalized by results of the analysis of the relevant statistical data. The results of the corresponding calculations showed that players tried not to execute serves in the 4th, 5th and 6th conditional zones because the rival's players are there who after serve receiving in most cases precisely addressed a ball to the partner for the organization of attack in reply. Power jump serves weren't also given to 1, 2 and 3 zones, and their greatest number was sent to the 8 and 9 zones. The direction of aimed serve generally concentrated in the 8th and also the 2nd zones of the playground. The assessment of indicators of serve efficiency, which were directed to different conditional zones of the court, is carried-out. Conclusions: the technique for carrying out the analysis of statistical data concerning execution of different ways of serves in beach volleyball competitions and assessment of the corresponding quantitative indicators of their execution efficiency is generalized. The results can be used in solving the problem of increase in execution efficiency of serves in the course of training and competitive activities of beach volleyball teams.